State Responsibility in Child Protection: A Fiqh Siyasah Perspective on Law No. 35/2014 Child Protection Law and State Responsibility - Sofiyana Nasution; Maulidya Mora Matondang (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This research is motivated by the increasing number of cases of violence against children in elementary schools, which indicates a gap between legal provisions and their implementation in the field. This study aims to analyze the state's responsibility in protecting the constitutional rights of elementary school children based on Article 54 of Law Number 35 of 2014 and examine its relevance from a jurisprudence perspective. This research uses a normative legal method by applying a statutory and conceptual approach. The results show that the implementation of child protection in elementary schools is still suboptimal, as indicated by the high rate of violence against children. This condition is influenced by weak supervision, ineffective coordination between institutions, and the less than optimal implementation requires further strengthening of siyasah dusturiyah aspects to ensure more substantive welfare (al-maslahah). Specific findings indicate a synchronization gap between child protection regulations and the fulfillment of fundamental rights within educational environments, where the principle of the state as a guardian (waliyul amri) has not been fully integrated into the technical and operational dimensions of field policy. This analysis asserts that reinforcing state responsibility must rely not only on the formal legality of positive law but also on the moral-political obligation to cultivate an educational ecosystem that is both secure and equitable, in alignment with the principles of himayah al-atfal. Therefore, it is necessary to strengthen the supervisory system, improve coordination between institutions, and develop more responsive and sustainable policies to ensure the effective protection of elementary school children.